Nigeria’s Foreign Policy, Reciprocity and Africa Centeredness: The Need for a Reconstruction in the 21st Century - Kia, Bariledum; Udeoji, Ebele Angela (Advances in Social Sciences Research Journal, 2020)
Nigeria foreign policy in the 21st century has attracted a great deal of attention, as the dynamics on the world stage and domestic realities continue to impose challenges for the citizens. While many countries have appreciated the new realities of world politics and have however adjusted to the new global situations, Nigeria is yet to adjust her foreign policy with domestic realities. Thus, the study explores Nigeria’s Africa centeredness’ policy with the view to ascertain its relevance or otherwise in the 21st century. Descriptive research method with explanatory variant are used. Findings show that, for as long as the objective of Nigeria’s foreign policy is to ensure protection of black and African interest, Nigeria cannot but find it necessary to offer solidarity with African states. However, because very little has happened to show that she has made so much sacrifice in African affairs, the study recommends amongst others that the scope of Nigeria’s reciprocity should be restricted to issues that are more apparently in consonance with her national interest.